Representations and geometric structures - Wienhard, Anna (Arxiv, 2016)
This note summarizes in an informal way some geometric properties of Anosov representations into the symplectic group, which were presented in a talk at the conference What is Next. The mathematical legacy of Bill Thurston, held in June 2014 in Cornell.
Gesehen am 14.02.2019